Analysis Of The Effect Of Corrosion Rate On Material Strength Of Ship Hull Steel Plat - Kresno Yuntoro; Ali Muktar Sitompul; Lilik Budiyanto; Mariana Kristianti; Devout Prakoso Trismianto (Applied Quantitative Analysis, 2026)
As a vast maritime nation, Indonesia relies heavily on sea transportation, where ships play a critical and indispensable role in maintaining inter-island connectivity and supporting national economic development. However, prolonged exposure of a ship's hull to the harsh marine environment makes the material highly susceptible to electrochemical corrosion. This degradation can significantly compromise the vessel's structural integrity, increase maintenance costs, and threaten operational safety at sea. One of the most effective and widely implemented corrosion protection techniques in the maritime industry is the galvanic cathodic protection system using sacrificial anodes, with zinc (Zn) being a frequently utilized material due to its favorable driving voltage and reliability in seawater. This study specifically investigates and analyzes the corrosion rate and surface morphology changes of zinc anodes installed on various sections of a 1200 DWT Ro-Ro vessel over a comprehensive one-year monitoring period. The research employed weight-loss measurements to determine the precise corrosion rate, while the microstructural surface morphology and elemental composition were analyzed in detail using Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDS). The empirical results and data analysis indicate a significant variation in corrosion rates depending on the anode's placement. The highest corrosion rate was observed on the anodes at the vessel's stern, reaching 2.6 mpy, whereas the lowest rate was recorded in the mid-hull section at 0.254 mpy. This disparity is primarily attributed to the complex hydrodynamic conditions around the hull; specifically, the high water turbulence and increased dissolved oxygen concentration near the stern caused by continuous propeller rotation accelerate the anodic dissolution process. Further compositional analysis revealed that aluminum oxide (Al2O3) was the dominant corrosion product, accounting for approximately 46.74% of the total anode material content. SEM observations identified localized pitting and cavity corrosion patterns; nevertheless, more than 50% of the overall anode surface remained electrochemically active and intact after one year of installation. These findings provide essential practical insights for naval architects and ship owners in predicting anode service life, planning material replacement, and optimizing maintenance schedules for marine cathodic protection systems. Future research is recommended to explore the synergistic influence of other environmental parameters, such as salinity, seawater temperature, and vessel operational speed, on the long-term performance of sacrificial anodes.